The G protein-coupled receptor regulatory kinase GPRK2 participates in Hedgehog signaling in Drosophila. - Molnar, C.; Holguin, H.; Mayor, F.; Ruiz-Gomez, A.; de Celis, J.F. (Proceedings of the National Academy of Sciences of the United States of America, 2007)
Signaling by Smoothened (Smo) plays fundamental roles during animal development and is deregulated in a variety of human cancers. Smo is a transmembrane protein with a heptahelical topology characteristic of G protein-coupled receptors. Despite such similarity, the mechanisms regulating Smo signaling are not fully understood. We show that Gprk2, a Drosophila member of the G protein-coupled receptor kinases, plays a key role in the Smo signal transduction pathway. Lowering Gprk2 levels in the wing disc reduces the expression of Smo targets and causes a phenotype reminiscent of loss of Smo function. We found that Gprk2 function is required for transducing the Smo signal and that when Gprk2 levels are lowered, Smo still accumulates at the cell membrane, but its activation is reduced. Interestingly, the expression of Gprk2 in the wing disc is regulated in part by Smo, generating a positive feedback loop that maintains high Smo activity close to the anterior-posterior compartment boundary.